Nickel Foam Supported NiO@Ru Heterostructure Towards High‐Efficiency Overall Water Splitting. Issue 17 (16th July 2021) - Zhang, Linghui; Hu, Zheng; Li, Hui; Ren, Qianqian; Qiu, Yishu; Qu, Jianqiang; Hu, Shi
Abstract: Electrocatalytic water splitting for hydrogen production from renewable energy requires the innovation of electrocatalysts with high activity and low cost. In this work, densely packed NiO@Ru nanosheets were fabricated on the surface of Ni foam through a two‐step method of Ni(OH)2 growth followed by Ru deposition. Through pair distribution function analysis from selected‐area electron diffraction and X‐ray photoelectron spectroscopy, the interface structure feature is revealed as a thin layer of perovskite NiRuO3 sandwiched between NiO and Ru. The electrode exhibits high activity and durability for HER and OER, delivering a current density of 10 mA cm −2 at a voltage of 1.55 V for overall water splitting in 1 M KOH. The excellent performance can be attributed to the intimate interface contact of NiO and Ru in addition to low charge transfer resistance and super‐hydrophilic surface structure, as verified by the electrochemical impedance spectroscopy and contact‐angle measurement. Abstract : NiO@Ru nanosheets with NiRuO3 interface is constructed on Ni foam by two‐step method of Cl − corrosion followed by Ru deposition. This self‐supported electrode with low Ru loading amount exhibits excellent performance toward overall water splitting in alkaline due to intimate interface contact, low impedance, and high surface hydrophilicity.